Application Of Spons Callispongia Sp Origin Of Halong Water (Ambon Bay) As Biomonitoring Contamination Trace Metals Pb,Cr,Cr And Zn - Siahaya, Antho Netty; Noor, Alfian; Soekamto, Nunuk H. (Indonesian Journal of Chemical Research, 2014)
The purpose of research it is cycles how knowing cycle trace metals Pb, Cd, Cr and Zn in Callispongia Sp, sediment and water. Techniques of the analysis of trace metals use ICP-OES ((Inductively Coupled Plasma Optical Emission Spectroscopy). Analysis dramatic of the relationship between sponge significant sediment and water show that highest trace metal is Zn to Callispongia sp (6.250 mg/kg dry weight), sediment (0.750 ppm and water 0.790 ppm)